How do you multiply (-1+2i)(3-i) in trigonometric form?

1 Answer
Apr 13, 2016

(-1+2i)*(3-i)=sqrt50[cosarctan(-7)+isinarctan(-7)]

Explanation:

We first covert them into trigonometric form. In this form a+bi=r(costheta+isintheta) or a+bi=r*e^(itheta), where r=sqrt(a^2+b^2) and theta=arctan(b/a)

Hence, -1+2i=sqrt5e^(ialpha), where alpha=arctan(-2)

and 3-i=sqrt10e^(ibeta), where beta=arctan(-1/3)

Hence (-1+2i)*(3-i)=sqrt50e^(i(alpha+beta))

As tan(alpha+beta)=(tanalpha+tanbeta)/(1-tanalpha*tanbeta) or

tan(alpha+beta)=((-2)-1/3)/(1-(-2)*(-1/3))=(-7/3)/(1-2/3)=(-7/3)/(1/3)=-7

Hence (-1+2i)*(3-i)=sqrt50e^(i(arctan(-7)))

or (-1+2i)*(3-i)=sqrt50[cosarctan(-7)+isinarctan(-7)]